2022
DOI: 10.3390/plants11233233
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparison of Bioactive Components of Two Dryopteris sp. Extract Using LC-QTOF-MS

Abstract: Dryopteris sp. is known for its various pharmacological effects and is used as a traditional medicine in Asia. The present study investigated the chemical composition and antimicrobial activity of Dryopteris sp. distributed in Korea. The chemical compounds in the ethanolic extracts of Dryopteris lacera and Dryopteris bissetiana were investigated by ultra-high performance liquid chromatography–quadrupole time-of-flight–mass spectrometry analysis and identified by exploring the UNIFI traditional medicine library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Compounds 30 and 31 had been tentatively identified as astragalin 7-rhamnoside ([M – H] − m / z 593.1486) and (3″-apiosyl-6″-malonyl)astragalin ([M – H] − m / z 725.144) in the CWR, the TWR, the TWF, and the BWF, respectively, in our study. In previous research, this compound was identified in Hibiscus mutabilis L. 67 and Dryopteris sp., 68 which has been proven to be able to inhibit the growth of liver cancer, 69 as well as to inhibit the proliferation of lung cancer. 70 Compounds 32 and 33 were identified in the TWR, TWF, and CWF samples as apigenin 7-glucoside and luteolin 4′- O -glucoside with the precursor ion [M – H] − m / z 431.0968 and [M – H] − m / z 447.0941, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 30 and 31 had been tentatively identified as astragalin 7-rhamnoside ([M – H] − m / z 593.1486) and (3″-apiosyl-6″-malonyl)astragalin ([M – H] − m / z 725.144) in the CWR, the TWR, the TWF, and the BWF, respectively, in our study. In previous research, this compound was identified in Hibiscus mutabilis L. 67 and Dryopteris sp., 68 which has been proven to be able to inhibit the growth of liver cancer, 69 as well as to inhibit the proliferation of lung cancer. 70 Compounds 32 and 33 were identified in the TWR, TWF, and CWF samples as apigenin 7-glucoside and luteolin 4′- O -glucoside with the precursor ion [M – H] − m / z 431.0968 and [M – H] − m / z 447.0941, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This Special Issue has published several articles pertaining to the extraction, characterization, and bio-activity evaluation of natural products derived from various plants. In one communication, Kim et al (2022) [1] employed LC-QTOF-MS to characterize the bioactive constituents of Dryopteris sp. extracts from two Korean species (Dryopteris lacera and Dryopteris bissetiana).…”
mentioning
confidence: 99%